The Impact of Online Social Media Marketing on Technology Access Among the Elderly in Thailand - U-Thairatana, Pichaya; Thanathavornkit, Chaiporn; Supunpong, Worraseth; Tareerak, Thammarat; Tipchareon, Sirinan (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
This research has two main objectives: (1) to study the access to technology of the elderly in Thailand, categorized by individual characteristics, and (2) to examine the impact of online social media marketing on the technology access of the elderly in Thailand. We collected data from elderly individuals aged 60-75 years through quota sampling, gathering a sample size of 480 individuals. The statistics used in the data analysis include percentage, mean, standard deviation, t-test, one-way analysis of variance, and multiple regression analysis. The research findings are: 1. The access to technology among the elderly in Thailand significantly differs statistically in terms of education level and average monthly income. 2. The factors in online social media marketing that affect the technology access of the elderly in Thailand include Promotion and Engagement (b= 0.33), Information and Assistance (b=0.19), Advice and Selling Products (b= 0.15), Customer Retention (b= 0.12), and Service and Support (b= 0.06), in that order. The equation has a predictive power of 72.60%, and can be written as follows: Ytot = 0.66+0.33X1**+0.19X2**+0.15X3**+0.06X4**+0.12X5** Article history: Received 25 April 2023 Revised 28 September 2023 Accepted 2 October 2023 SIMILARITY INDEX = 9.84 %